Desentralisasi dan Akses Pendidikan Dasar di Indonesia - Mustawaniyah, Miro'atul (Jurnal Administrasi Publik, 2015)
Abstract:Decentralization and Access of Basic Education in Indonesia. This research aims to explain and analyze the link between decentralization and basic education access in Indonesia. Basic education access is measured by Net Enrollment Rate (NER) for elementary school and junior high schools. Fiscal decentralisation is measured by general allocation fund (DAU), revenue (PAD) and district education budget, administrative decentralisation is measured by distribution of teacher both in elementary school and junior high school, and political decentralisation is measured by age of local election. This research is belong to explanatory research by using quantitative approach. Population in this research is all kabupaten/kota in Indonesia 2014. The analysis in this research use descriptive statistic to describe basic education access in Indonesia and bivariate correlation analysis to test the relationship between decentralization variables and NER. The results show that persistence of the wide gap between kabupaten/kota in Pulau Jawa and kabupaten/kota Pulau Jawa, especially Propinsi Papua after nearly fifteen years of Indonesia implementing decentralisation. Results of correlation analysis show that factors associated with the elementary NER and junior high schools NER are general allocation fund, district own revenue, district education budget, number of elementary school teachers, and age of democracy. However, the factors of junior high school NER are district own revenue, district education budget, and number of teachers junior high schools. Keywords:decentralization, basic education access, indonesia Â  Abstrak:Desentralisasi dan Akses Pendidikan Dasar di Indonesia. Penelitian ini bertujuan untuk menjelaskan dan menganalisis hubungan desentralisasi dan akses pendidikan dasar di Indonesia. Akses pendidikan dasar diukur dari APM SD/MI dan APM SMP/MTs tahun 2014. Desentralisasi diukur dari desentralisasi fiskal yang terdiri dari (DAU, PAD, dan anggaran pendidikan), desentralisasi administrasi yang terdiri dari (jumlah guru SD/MI dan guru SMP/MTs), dan desentralisasi politik yang terdiri dari usia Pilkada. Jenis penelitian yang digunakan adalah jenis penelitian eksplanatori dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh kabupaten/kota di Indonesia tahun 2014. Analisis dalam penelitian ini menggunakan statistik deskriptif untuk menggambarkan akses pendidikan dasar di Indonesia dan analisis korelasi untuk menghubungkan antara variabel-variabel desentralisasi dan APM. Hasil penelitian ini menunjukkan masih adanya kesenjangan yang lebar antara kabupaten/kota di Pulau Jawa dan beberapa kabupaten/kota di luar Pulau Jawa khususnya Propinsi Papua setelah hampir lima belas tahun Indonesia menjalankan desentralisasi. Hasil analisis korelasi menunjukkan faktor-faktor yang berhubungan dengan APM SD/MI dan APM SMP/MTs yaitu DAU, PAD, anggaran pendidikan, jumlah guru SD/MI, dan usia Pilkada berhubungan APM SD. Sedangkan, faktor-faktor yang berhubungan dengan APM SMP/MTs adalah PAD, anggaran pendidikan, dan jumlah guru SMP/MTs. Â  Kata kunci:desentralisasi, akses pendidikan dasar, indonesiaÂ